CONTROVERSY ON THE TERMINATION OF LARGE-SCALE SOCIAL RESTRICTIONS IN GREATER SURABAYA AT KOMPAS.COM AND SUARASURABAYA.NET - Ruri Handariastuti; Zainal Abidin Achmad (Universitas Islam Balitar, 2020)
East Java Governor Khofifah Indar Parawansa officially imposed the termination of PSBB Surabaya Raya on June 8, 2020. The decision based on the agreement of three leaders of the Greater Surabaya region (Surabaya, Sidoarjo, and Gresik). The agreement to stop the PSBB caused controversy in the community because, based on statistics, the definite number of COVID-19 cases is still very high in the three regions. It is still not feasible to stop the PSBB. This study uses the analysis method of Framing Pan and Kosicki by basing on a constructive paradigm and media representation. This method assumes that every news has a frame that functions as the center of organizational ideas. News in both media has not fully used the elements of 5H and 1H and display photos that are not following the news contents. As a result, suarasurabaya.net mostly constructs the existence of East Java Governor's disapproval of the termination of the PSBB policy in Greater Surabaya based on one source. Whereas Kompas.com is more multi-perspective, displaying reasons for the termination of PSBB because of many display sources of interviews.